Vaccinia virus-mediated melanin production allows MR and optoacoustic deep tissue imaging and laser-induced thermotherapy of cancer - Stritzker, Jochen; Kirscher, Lorenz; Scadeng, Miriam; Deliolanis, Nikolaos C.; Morscher, Stefan; Symvoulidis, Panagiotis; Schaefer, Karin; Zhang, Qian; Buckel, Lisa; Hess, Michael; Donat, Ulrike; Bradley, William G.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
We reported earlier the delivery of antiangiogenic single chain antibodies by using oncolytic vaccinia virus strains to enhance their therapeutic efficacy. Here, we provide evidence that gene-evoked production of melanin can be used as a therapeutic and diagnostic mediator, as exemplified by insertion of only one or two genes into the genome of an oncolytic vaccinia virus strain.We found that produced melanin is an excellent reporter for optical imaging without addition of substrate.Melanin production also facilitated deep tissue optoacoustic imaging as well asMRI. In addition,melanin was shown to be a suitable target for laser-induced thermotherapy and enhanced oncolytic viral therapy. In conclusion, melanin as a mediator for thermotherapy and reporter for different imaging modalities may soon become a versatile alternative to replace fluorescent proteins also in other biological systems. After ongoing extensive preclinical studies, melanin overproducing oncolytic virus strainsmight be used in clinical trials in patients with cancer.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Diagnosis; Personalized medicine; Photoacoustic; Translational medicine; Whole-body imaging